2021
DOI: 10.31224/osf.io/c974v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive model predictive control for actuation dynamics compensation in real-time hybrid simulation

Abstract: Real-time hybrid simulation is an experimental method used to obtain the dynamic response of a system whose components consist of loading-rate-sensitive physical and numerical substructures. The coupling of these substructures is achieved by actuation systems, i.e., an arrangement of motors or actuators, which are responsible for continuously synchronizing the interfaces of the substructures and are commanded in closed-loop control setting. To ensure high fidelity of such hybrid simulations, performing them in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies have been carried out using model predictive control (MPC) strategy (Yang et al, 2017;Pereida and Schoellig, 2018;Malalis et al, 2020). Tsokanas et al first confirmed the promising tracking performance and robustness of MPC in RTHS application (Tsokanas et al, 2020(Tsokanas et al, , 2021(Tsokanas et al, , 2022. Traditional and adaptive MPC combined with Kalman filter were proposed to predict the future plant states and handle the nonlinear system dynamics (Shao et al, 2022;Tsokanas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out using model predictive control (MPC) strategy (Yang et al, 2017;Pereida and Schoellig, 2018;Malalis et al, 2020). Tsokanas et al first confirmed the promising tracking performance and robustness of MPC in RTHS application (Tsokanas et al, 2020(Tsokanas et al, , 2021(Tsokanas et al, , 2022. Traditional and adaptive MPC combined with Kalman filter were proposed to predict the future plant states and handle the nonlinear system dynamics (Shao et al, 2022;Tsokanas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…From the coupling of substructures, several challenges arise, e.g., time delays due to inherent transfer system dynamics or due to computational power needed to compute the NS response. Advanced control techniques [1][2][3][4] and model order reduction methods [5,6] have been used to tackle such issues. Albeit the challenges, the HS approach is beneficial since it can be used to experimentally study the inner workings of specific substructures over their linear regime and, hence, acquire realistic results but without constructing the entire considered system nor risking damaging it.…”
Section: Introductionmentioning
confidence: 99%
“…time delays due to inherent transfer system dynamics or due to computational power needed to compute the NS response. Advance control techniques [1,2] and model order reduction methods [3,4] have been used to tackle such issues. Albeit the challenges, the HS approach is beneficial since it can be used to experimentally study the inner workings of specific substructures over their linear regime and hence acquire realistic results but without constructing the entire considered system nor risking damaging it.…”
Section: Introductionmentioning
confidence: 99%